Design method, preparation method and application of ammonium ion battery electrolyte additive adaptive to high-voltage Prussian blue positive electrode material

The suitable electrostatic potential of aprotic solvent was determined through quantum chemometry, and acetone was selected as the electrolyte additive to construct a competitive water-depleted solvation structure, which solved the problem of limiting the electrochemical stability window of water decomposition reaction in water-based batteries, and achieved the stable cycle performance of high-voltage Prussian blue positive electrode material and the stability of the electrode structure.

CN119864517APending Publication Date: 2025-04-22LIAONING UNIVERSITY
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411909027.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-22

Smart Images

  • Figure CN119864517A_ABST
    Figure CN119864517A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of sustainable battery electrolyte design, is applied to an aqueous ammonium ion energy storage system, and particularly relates to a design method and a preparation method of an ammonium ion battery electrolyte additive adaptive to a high-voltage Prussian blue positive electrode material. According to the design method, electrostatic potentials (ESP) of different aprotic solvents are compared through quantum chemistry calculation, and finally acetone (ACE) is selected as an electrolyte additive to construct a weak solvation electrolyte system based on hydrogen bond interaction. The saturated addition amount of acetone in 1.0 mol L <-1 > (NH4) 2SO4 aqueous solution is determined through a pre-experiment, and is marked as 25% ACE. The electrolyte shows high suitability with a high-voltage Prussian blue positive electrode material (N-VHCF). Benefited from the construction of a competitive water-poor solvation structure and the blocking of a hydrogen bond network, the hydrogen evolution reaction and the oxygen evolution reaction in a 25% ACE electrolyte are inhibited, and the excellent performance of the Prussian blue positive electrode material (N-VHCF) under high discharge voltage is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sustainable battery electrolyte design, and specifically relates to a design method of an ammonium ion battery electrolyte additive suitable for high-voltage Prussian blue positive electrode material, a preparation method and an application thereof. Background Art

[0002] Aqueous rechargeable batteries have attracted much attention due to their high safety, environmental friendliness and low cost. However, the decomposition of water in aqueous electrolytes (hydrogen evolution reaction and oxygen evolution reaction) is an inevitable problem, which significantly limits the electrochemical stability window and hinders the application of high-voltage positive electrodes. The series of side reactions caused by it lead to a decrease in battery cycle performance and even dissolution and crushing of the electrode structure. Although a large number of studies on electrolyte improvement have emerged in aqueous battery systems with metal charge carriers, including solvation structure regulation and hydrogen bond network blockade. However, the non-metallic charge carrier NH4 + It has interesting properties different from metal charge carriers, especially the unique hydrogen bonding chemical mechanism. Therefore, readjusting the hydrogen bonding configuration in aqueous ammonium ion battery electrolytes is expected to solve a series of negative effects caused by water decomposition in the system. Since aprotic solvents only contain hydrogen bond acceptors but no hydrogen bond donors, they are introduced as additives into ammonium ion battery electrolyte systems to make NH4 + The competitive water-poor solvation structure is formed and the continuous water hydrogen bond network is blocked. Here, a method for designing electrolyte additives for ammonium ion batteries suitable for high-voltage Prussian blue cathode materials is developed. First, the electrostatic potential (ESP) of a series of aprotic solvents is determined by quantum chemical calculations. The hydrogen bonding effect determines the NH4 + The more negative ESP value leads to stronger solvation ability, which also means that it is easier to enter NH4 + Secondly, acetone with an ESP value slightly greater than that of water was selected as an electrolyte additive to construct a competitive water-poor solvation structure and achieve the blockade of the hydrogen bond network in the system. Finally, the designed electrolyte (25% ACE) was applied to a high discharge voltage Prussian blue cathode, and compared with a pure water system electrolyte (0% ACE), an excellent and stable electrochemical ammonium storage performance was achieved. Summary of the invention

[0003] The purpose of the present invention is to provide an ammonium ion battery electrolyte additive design method suitable for high-voltage Prussian blue positive electrode materials. The electrostatic potential (ESP) of a series of aprotic solvents is determined by quantum chemical calculations, and an acetone (ACE) additive is selected to construct a weakly solvated electrolyte (25% ACE), thereby proving its perfect adaptation to the high-voltage Prussian blue positive electrode material.

[0004] To achieve the above object, the technical solution adopted by the present invention is:

[0005] A method for designing an ammonium ion battery electrolyte additive suitable for a high-voltage Prussian blue positive electrode material comprises the following steps:

[0006] 1) Calculate and compare the electrostatic potential ESP of different aprotic solvents by quantum chemistry: select six aprotic solvents with different functional groups, namely dimethyl sulfoxide, N,N-dimethylformamide, ethylene glycol dimethyl ether, acetone, acetonitrile and propylene carbonate, and calculate their ESP values ​​by quantum chemistry;

[0007] 2) The ESPs of the six aprotic solvents obtained by calculation were compared with the ESP of water, and aprotic solvents with ESP values ​​slightly higher than that of water were selected as electrolyte additives to construct a competitive water-poor solvation structure;

[0008] 3) Determine the selected aprotic solvent additive at 1.0 mol L -1 The saturated addition amount in the (NH4)2SO4 aqueous solution.

[0009] Furthermore, in the above-mentioned method for designing an ammonium ion battery electrolyte additive suitable for high-voltage Prussian blue positive electrode material, in step 1), the ESP calculation of the aprotic solvent is performed using the Gaussian 09 program package, using the DFT method, at the B3LYP level and the 6-311+G(d,p) basis set.

[0010] An ammonium ion battery electrolyte suitable for high-voltage Prussian blue positive electrode material designed based on any of the above-mentioned design methods, the preparation method of which is as follows: acetone is added as an additive to 1.0 mol L -1 The electrolyte is formed in an aqueous solution of (NH4)2SO4. The saturated amount of acetone added to the electrolyte is 25% by volume. The electrolyte is recorded as 1.0 mol L -1 (NH4)2SO4@25%ACE.

[0011] The above 1.0 mol L -1 Application of (NH4)2SO4@25% ACE electrolyte in ammonium ion batteries with high-voltage Prussian blue cathode material.

[0012] Further, the above application method is as follows: using NH4-rich + The vanadium-based Prussian blue electrode was used as the positive electrode, the calomel electrode was used as the reference electrode, and the graphite foil was used as the counter electrode. -1 (NH4)2SO4@25% ACE is used as the electrolyte to form an ammonium ion battery with high-voltage Prussian blue as the positive electrode material.

[0013] Furthermore, in the above application, the NH4-rich+ The preparation method of the vanadium-based Prussian blue electrode comprises the following steps: in N-methylpyrrolidone solvent, + The vanadium-based Prussian blue positive electrode material was evenly mixed with acetylene black and polyvinylidene fluoride binder to form a slurry, which was then evenly coated on a 0.3 mm thick titanium foil and dried at 60°C overnight.

[0014] Preferably, the above-mentioned NH4-rich + Preparation method of vanadium-based Prussian blue electrode, rich in NH4 + The vanadium-based Prussian blue positive electrode material is mixed with acetylene black and polyvinylidene fluoride binder in a weight ratio of 7:2:1.

[0015] Preferably, the above-mentioned NH4-rich + Preparation method of vanadium-based Prussian blue electrode, the NH4-rich + The average loading amount of the vanadium-based Prussian blue positive electrode material on the titanium foil is 1 to 1.5 mg.

[0016] Furthermore, the above NH4-rich + Preparation method of vanadium-based Prussian blue electrode, the NH4-rich + The preparation method of the vanadium-based Prussian blue positive electrode material comprises the following steps:

[0017] 1) Dissolve 0.4 g of ammonium metavanadate, 0.8 g of potassium ferrocyanide and 1.2 g of oxalic acid in 80 mL of deionized water and stir evenly at room temperature until a uniform and transparent solution is formed, which is the precursor solution;

[0018] 2) placing the obtained precursor solution in a high temperature oven for hydrothermal reaction, cooling to room temperature, washing the obtained solution by centrifugation, and then vacuum drying at 60° C. for 12 h, and the obtained dark blue powder is a vanadium-based Prussian blue positive electrode material;

[0019] 3) Take 0.5g of vanadium-based Prussian blue positive electrode material powder and dissolve it in 1.0mol L -1 (NH4)2SO4 aqueous solution, magnetically stirred for 24h, centrifuged and washed, and then vacuum dried at 60℃ for 12h to finally obtain NH4-rich + Vanadium-based Prussian blue positive electrode material.

[0020] Preferably, the above-mentioned NH4-rich + A method for preparing a vanadium-based Prussian blue positive electrode material, in step 2), the conditions of the hydrothermal reaction are: reacting at 180° C. for 8 hours.

[0021] The beneficial effects of the present invention are:

[0022] 1. The electrostatic potential (ESP) of a series of aprotic solvents is determined by quantum chemical calculation methods, and used as a descriptor for additives in aqueous ammonium ion battery electrolyte systems dominated by hydrogen bonding interactions. Specifically, more negative ESP values ​​represent stronger solvation ability, because NH4 + The solvation structure in the pure water system forms four hydrogen bonds with water. Therefore, selecting an aprotic solvent with an ESP value close to that of water can form a competitive water-poor solvation structure and at the same time block the continuous H2O-H2O hydrogen bond network in the system.

[0023] 2. The weakly solvated electrolyte determined by the present invention is based on 1.0 mol L -1 The saturated addition of acetone (25% ACE) in the (NH4)2SO4 aqueous solution shows perfect compatibility with the high-voltage Prussian blue cathode. Specifically, it effectively inhibits the decomposition of water (hydrogen evolution reaction and oxygen evolution reaction) in the aqueous electrolyte system, broadens the electrochemical stability window, inhibits the problem of electrode life limitation caused by the dissolution of transition metal ions in vanadium-based Prussian blue, and realizes the reversible and stable charge and discharge process of the high-voltage Prussian blue cathode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 : is the electrostatic potential energy surface diagram of different aprotic solvents obtained by quantum chemical calculation in Example 1.

[0025] Figure 2 The 1.0 mol L -1 Optical photograph of saturated addition of acetone in (NH4)2SO4 aqueous solution.

[0026] Figure 3 These are scanning electron microscope images of the N-VHCF positive electrode material prepared in Example 2 at different magnifications.

[0027] Figure 4 It is a comparison diagram of constant current charge and discharge curves of N-VHCF positive electrode in 0% ACE and 25% ACE electrolytes at low current density in Example 3 and the comparative example.

[0028] Figure 5 In the figure a and b are respectively the constant current charge-discharge curve (a) and rate curve (b) of the N-VHCF positive electrode in 25% ACE electrolyte in Example 3.

[0029] Figure 6 Figures a and b are the constant current charge-discharge curve (a) and rate curve (b) of the N-VHCF positive electrode in the comparative example in 0% ACE electrolyte.

[0030] Figure 7It is a comparison diagram of the life span and coulomb efficiency curves of the N-VHCF positive electrode in 0% ACE and 25% ACE electrolytes at a low current density in Example 3 and the comparative example. DETAILED DESCRIPTION

[0031] Example 1

[0032] 1) Quantum chemical calculation of electrostatic potential (ESP) of different aprotic solvents: Six aprotic solvents with different functional groups were selected, namely dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF), ethylene glycol dimethyl ether (DME), acetone (ACE), acetonitrile (ACN) and propylene carbonate (PC), and their ESP values ​​were calculated by quantum chemistry. For the ESP calculation of aprotic solvents, the Gaussian 09 program package was used, using the DFT method, at the B3LYP level and the 6-311+G(d,p) basis set.

[0033] 2) According to the calculated ESP value, acetone (ACE) was selected as an electrolyte additive to construct a weakly solvated electrolyte.

[0034] 3) Preliminary experiments to investigate 1.0 mol L -1 Saturated amount of acetone added to (NH4)2SO4 aqueous solution: Dissolve 2.64g (NH4)2SO4 in 20mL deionized water to obtain a transparent uniform solution (recorded as 0% ACE). At this time, the concentration of (NH4)2SO4 is 1.0 mol L -1 Similarly, 2.64 g (NH4)2SO4 was dissolved in 16 mL, 15 mL, and 14 mL of deionized water, respectively. After stirring evenly, 4 mL, 5 mL, and 6 mL of acetone were added thereto, respectively. After stirring and ultrasonication for 30 min, electrolytes with different acetone contents were obtained, which were recorded as 20% ACE, 25% ACE, and 30% ACE, respectively.

[0035] Figure 1 The electrostatic potential energy surface diagram of different solvents obtained by quantum chemical calculation. According to the calculation results, the ESP of DMSO is -45.75 kcal mol -1 The ESP of DMF is -44.04 kcal mol -1 ACE's ESP is -36.81 kcalmol -1 , the ESP of DME is -35.30 kcal mol -1 , the ESP of ACN is -30.05 kcal mol -1 , the ESP of PC is -39.93 kcalmol -1 , the ESP of H2O is -37.30 kcal mol -1Among them, the ESP value of ACE is similar to that of H2O and slightly larger than that of H2O. Therefore, ACE is selected as an aqueous electrolyte additive to construct a competitive water-poor solvation structure.

[0036] Figure 2 The 1.0 mol L -1 Optical photograph of acetone added to (NH4)2SO4 aqueous solution at saturated concentration. When the volume percentage of ACE is 30% v / v, obvious stratification can be observed. -1 The saturated addition amount of (NH4)2SO4 in the aqueous solution is 25% v / v, and the electrolyte is recorded as 1.0 mol L -1 (NH4)2SO4@25%ACE.

[0037] Example 2

[0038] 1) Prepare a precursor solution for hydrothermal reaction: dissolve 0.4 g ammonium metavanadate, 0.8 g potassium ferrocyanide and 1.2 g oxalic acid in 80 mL deionized water, and stir evenly at room temperature until a uniform and transparent solution is generated, which is the precursor solution.

[0039] 2) Hydrothermal synthesis of vanadium-based Prussian blue cathode material (K-VHCF): The obtained precursor solution was placed in a high-temperature oven at 180°C for reaction for 8 hours; after cooling to room temperature, the obtained solution was washed three times with deionized water and ethanol respectively by centrifugation, and then the obtained solid was vacuum dried at 60°C for 12 hours to obtain K-VHCF dark blue powder.

[0040] 3) Synthesis of NH4-rich + Vanadium-based Prussian blue cathode material (N-VHCF): 0.5 g K-VHCF powder was dissolved in 1.0 mol L -1 In (NH4)2SO4 aqueous solution, after magnetic stirring for 24 hours, centrifugal washing, and then vacuum drying at 60°C for 12 hours, N-VHCF positive electrode material was finally obtained.

[0041] 4) Preparation of N-VHCF electrode: In N-methylpyrrolidone (NMP) solvent, N-VHCF positive electrode material, acetylene black and polyvinylidene fluoride binder (PVDF) were uniformly mixed in a weight ratio of 7:2:1 to form a slurry; the slurry was then uniformly coated on a 0.3 mm thick titanium foil and dried at 60°C overnight. The average loading amount of the N-VHCF positive electrode material was 1 to 1.5 mg.

[0042] Figure 3 Figures a and b are SEM images of the prepared N-VHCF cathode material at different magnifications. Figure 3As can be seen in a and b, unlike the conventional Prussian blue cubic structure, the N-VHCF stacking presents a nanoflower-like morphology.

[0043] Example 3

[0044] 1.0 mol L -1 Study on the compatibility of (NH4)2SO4@25% ACE electrolyte with high-voltage Prussian blue cathode material in aqueous ammonium ion batteries.

[0045] Methods: The electrochemical tests were carried out in a Swagelok cell with N-VHCF electrode as the positive electrode, calomel electrode as the reference electrode, graphite foil as the counter electrode, and 1.0 mol L -1 (NH4)2SO4@25% ACE was used as the electrolyte, and constant current charge-discharge test and life test were performed on N-VHCF in the voltage window of -0.5~1.3V.

[0046] Comparative Example

[0047] Study on the compatibility of 0% ACE electrolyte with high-voltage Prussian blue cathode material in aqueous ammonium ion batteries.

[0048] Methods: The electrochemical tests were carried out in a Swagelok cell with N-VHCF electrode as the positive electrode, calomel electrode as the reference electrode, graphite foil as the counter electrode, and 1.0 mol L -1 (NH4)2SO4 was used as the electrolyte, and constant current charge and discharge tests and life tests were performed on N-VHCF in the voltage window of -0.5 to 1.3V.

[0049] Figure 4 The constant current charge and discharge curves of N-VHCF cathode in 0% ACE and 25% ACE electrolytes at low current density are compared. Figure 4 It can be seen that at a small current density of 1Ag -1 When the N-VHCF cathode in 0% ACE electrolyte was charged to 1.3 V, a serious oxygen evolution reaction occurred, and the specific capacity was 75 mAh g -1 In the 25% ACE electrolyte, the N-VHCF cathode did not undergo hydrogen evolution reaction and achieved a coulombic efficiency of ~100%, with the specific capacity increased to 92 mAh g -1 , showing a flat high discharge platform (~0.8V, ~0.2V). This result shows that the water decomposition reaction is effectively inhibited in the 25% ACE electrolyte.

[0050] Figure 5 Figures a and b are the constant current charge-discharge curve and rate curve of N-VHCF cathode in 25% ACE electrolyte. Figure 5It can be seen that in 25% ACE electrolyte, when the current density is 1A g -1 When N-VHCF has a specific capacity of 92 mAh g -1 ; When the current density increases from 1A g -1 Increase to 5Ag -1 The specific capacity is 55 mAh g -1 , showing excellent rate performance. It is worth noting that when returning to a low current density, the N-VHCF cathode can still provide the specific capacity of the initial state, showing a highly reversible charge and discharge process.

[0051] Figure 6 Figures a and b are the constant current charge-discharge curve and rate curve of N-VHCF cathode in 0% ACE electrolyte. Figure 6 It can be seen that in 0% ACE electrolyte, when the current density is 1Ag -1 When N-VHCF has a specific capacity of 78 mAh g -1 ; When the current density increases from 1A g -1 Increase to 5A g -1 The specific capacity is 40 mAh g -1 When the current density returns to a low level, the N-VHCF cathode still cannot provide the specific capacity at the initial state. It is worth noting that compared with the electrolyte in 25% A CE, the specific capacity at a low current density continues to decay, indicating that the charge and discharge process is highly irreversible.

[0052] Figure 7 The figure is a comparison of the life and coulomb efficiency curves of N-VHCF cathode in 0% ACE and 25% ACE electrolytes at low current density. Figure 7 It can be seen that in 25% ACE electrolyte, N-VHCF -1 After 100 cycles at a current density of 1.5 %, the N-VHCF cathode material showed an excellent capacity retention rate of 87.6%, and the coulombic efficiency was 100% during the whole process; while in 0% ACE, the capacity retention rate was only 15.5%, and the coulombic efficiency was very poor at 60%. It was proved that the 25% ACE electrolyte effectively reduced the activity of water, inhibited the dissolution of transition metal ions, and made the N-VHCF cathode material show excellent cycle stability.

Claims

1. A design method for an ammonium ion battery electrolyte additive suitable for high-voltage Prussian blue positive electrode material, characterized in that: The steps include: 1) Calculate and compare the electrostatic potential ESP of different aprotic solvents by quantum chemistry: select six aprotic solvents with different functional groups, namely dimethyl sulfoxide, N,N-dimethylformamide, ethylene glycol dimethyl ether, acetone, acetonitrile and propylene carbonate, and calculate their ESP values ​​by quantum chemistry; 2) The ESPs of the six aprotic solvents obtained by calculation were compared with the ESP of water, and aprotic solvents with ESP values ​​slightly higher than that of water were selected as electrolyte additives to construct a competitive water-poor solvation structure; 3) Determine the selected aprotic solvent additive at 1.0 mol L -1 The saturated addition amount in the (NH4)2SO4 aqueous solution.

2. The method for designing an ammonium ion battery electrolyte additive suitable for high-voltage Prussian blue positive electrode material according to claim 1, characterized in that: In step 1), the ESP calculations for aprotic solvents were performed using the Gaussian 09 program package, using the DFT method at the B3LYP level and the 6-311+G(d,p) basis set.

3. An ammonium ion battery electrolyte suitable for high-voltage Prussian blue positive electrode material designed based on the design method of claim 1 or 2, characterized in that: The preparation method is as follows: acetone is added as an additive to 1.0 mol L -1 The electrolyte is formed in an aqueous solution of (NH4)2SO4. The saturated amount of acetone added to the electrolyte is 25% by volume. The electrolyte is recorded as 1.0 mol L -1 (NH4)2SO4@25%ACE.

4. 1.0 mol L according to claim 3 -1 Application of (NH4)2SO4@25%ACE electrolyte in ammonium ion batteries with high-voltage Prussian blue cathode material.

5. The use according to claim 4, characterized in that: The method is as follows: using NH4-rich + The vanadium-based Prussian blue electrode was used as the positive electrode, the calomel electrode was used as the reference electrode, and the graphite foil was used as the counter electrode. -1 (NH4)2SO4@25%ACE is used as electrolyte to form an ammonium ion battery with high-voltage Prussian blue positive electrode material.

6. The use according to claim 5, characterized in that: The NH4-rich + The preparation method of the vanadium-based Prussian blue electrode comprises the following steps: in N-methylpyrrolidone solvent, + The vanadium-based Prussian blue positive electrode material was evenly mixed with acetylene black and polyvinylidene fluoride binder to form a slurry, which was then evenly coated on a 0.3 mm thick titanium foil and dried at 60°C overnight.

7. The use according to claim 6, characterized in that: Rich in NH4 + The vanadium-based Prussian blue positive electrode material is mixed with acetylene black and polyvinylidene fluoride binder in a weight ratio of 7:2:

1.

8. The use according to claim 6, characterized in that: The NH4-rich + The average loading amount of the vanadium-based Prussian blue positive electrode material on the titanium foil is 1 to 1.5 mg.

9. The use according to claim 6, characterized in that: The NH4-rich + The preparation method of the vanadium-based Prussian blue positive electrode material comprises the following steps: 1) Dissolve 0.4 g of ammonium metavanadate, 0.8 g of potassium ferrocyanide and 1.2 g of oxalic acid in 80 mL of deionized water and stir evenly at room temperature until a uniform and transparent solution is formed, which is the precursor solution; 2) placing the obtained precursor solution in a high temperature oven for hydrothermal reaction, cooling to room temperature, washing the obtained solution by centrifugation, and then vacuum drying at 60° C. for 12 h, and the obtained dark blue powder is a vanadium-based Prussian blue positive electrode material; 3) Take 0.5g of vanadium-based Prussian blue positive electrode material powder and dissolve it in 1.0mol L -1 (NH4)2SO4 aqueous solution, magnetically stirred for 24h, centrifuged and washed, and then vacuum dried at 60℃ for 12h to finally obtain NH4-rich + Vanadium-based Prussian blue positive electrode material.

10. The use according to claim 9, characterized in that: In step 2), the hydrothermal reaction conditions are: reaction at 180° C. for 8 h.

Citation Information

Cited By

  • Electrolyte, preparation method thereof and aqueous ammonium ion battery

    CN121726558A

  • Electrolyte, preparation method thereof and aqueous ammonium ion battery

    CN121726558B